2021
DOI: 10.3390/biom11071015
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Mimetic Nanozymes in Cancer Phototherapy: Progress and Perspectives

Abstract: Nanomaterial-mediated cancer therapeutics is a fast developing field and has been utilized in potential clinical applications. However, most effective therapies, such as photodynamic therapy (PDT) and radio therapy (RT), are strongly oxygen-dependent, which hinders their practical applications. Later on, several strategies were developed to overcome tumor hypoxia, such as oxygen carrier nanomaterials and oxygen generated nanomaterials. Among these, oxygen species generation on nanozymes, especially catalase (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 112 publications
0
27
0
Order By: Relevance
“…The enzymatic action of nanoparticles can lead to significant altering of the TME through various known or perceived mechanisms that include catalyzing Fenton-type reactions, cleaving prodrugs to locally release toxic drugs, degrading tumor-promoting oncogenes, duplicating the action of enzymes such as CAT, etc. [ 74 , 75 , 76 ]. Such nanozyme-mediated TME modulation can lead either to direct killing of cancer cells or complement other therapies such as chemotherapy, photothermal therapy (PTT), and photodynamic therapy (PDT).…”
Section: Nanozyme Platforms For Anticancer Applicationsmentioning
confidence: 99%
“…The enzymatic action of nanoparticles can lead to significant altering of the TME through various known or perceived mechanisms that include catalyzing Fenton-type reactions, cleaving prodrugs to locally release toxic drugs, degrading tumor-promoting oncogenes, duplicating the action of enzymes such as CAT, etc. [ 74 , 75 , 76 ]. Such nanozyme-mediated TME modulation can lead either to direct killing of cancer cells or complement other therapies such as chemotherapy, photothermal therapy (PTT), and photodynamic therapy (PDT).…”
Section: Nanozyme Platforms For Anticancer Applicationsmentioning
confidence: 99%
“…SAzyme with peroxidase activity (CAT) can oxidize endogenous H 2 O 2 to O 2 and alleviate cellular hypoxia. In addition, peroxidase activity can also catalyze the production of ROS, thus combining SAzyme with photodynamic therapy is a promising method for highly curative treatment of tumors [98] . Li Qiu′s group [31] synthesized a polymeric spherical nanozyme by self‐assembly reaction using 5,10,15,20‐tetrakis(4‐pyridyl) porphyrin and pyridine nitrogen‐containing substances as ligands and Pd atoms as linking sites.…”
Section: Biomedical Therapymentioning
confidence: 99%
“…In addition, peroxidase activity can also catalyze the production of ROS, thus combining SAzyme with photodynamic therapy is a promising method for highly curative treatment of tumors. [98] Li Qiu's group [31] synthesized a polymeric spherical nanozyme by self-assembly reaction using 5,10,15,20-tetrakis(4-pyridyl) porphyrin and pyridine nitrogen-containing substances as ligands and Pd atoms as linking sites. The POD-like enzymatic activity of this SAzyme can be significantly enhanced by ultrasound and light irradiation, resulting in favorable acoustodynamic and photodynamic therapeutic effects.…”
Section: Cancer Therapymentioning
confidence: 99%
“…The repeated administration of large amounts of active agent may increases the potential toxicity to biosystem [ 19 ]. Moreover, CeNP showed additional advantages, such as high efficiency, high versatility, high stable, low costs, and minimal immunogenicity [ 21 ]. We previously demonstrated that CeNP exhibited neuroprotective effects by suppressing the proinflammatory responses of activated microglia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%